1963
DOI: 10.1149/1.2425863
|View full text |Cite
|
Sign up to set email alerts
|

Electroluminescent Lines in ZnS Powder Particles

Abstract: Existing theories of ZnS-powder-EL are shown to be unable to explain the new findings of electroluminescent striations or lines described in Part I of this work. Several new hypotheses are discussed. Among these, a model seems to be likely which is based on simultaneous bipolar field-emission from opposite ends of conducting imperfection lines into the insulating crystallite, with trapping of injected holes in activator centers, and recombination with mobile electrons at field-reversal. This model, which is sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
84
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(87 citation statements)
references
References 37 publications
3
84
0
Order By: Relevance
“…On the basis of the previous studies [12,13] and results shown above, EL has been attributed to the ionization of activators by the impact of charge carriers accelerated by the high electric fields between Cu x S precipitates and ZnS:Cu,Cl matrix. It is believed that both the amount as well as the physical properties of Cu x S precipitates would influence the recombination rate and the following EL intensity.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…On the basis of the previous studies [12,13] and results shown above, EL has been attributed to the ionization of activators by the impact of charge carriers accelerated by the high electric fields between Cu x S precipitates and ZnS:Cu,Cl matrix. It is believed that both the amount as well as the physical properties of Cu x S precipitates would influence the recombination rate and the following EL intensity.…”
Section: Resultsmentioning
confidence: 83%
“…According to the bipolar field emission model proposed by Fischer [12,13], conductive impurities such as cuprous sulfides (Cu x S) are necessary for luminescent ZnS particles to intensify the electric field, and to allow holes and electrons to recombine with radiation in luminescent centers. Therefore, by referring to the XRD analysis shown above, we can also predict that the samples fired at 900 • C with Cu Figure 3 shows the EL emission spectra of ZnS:Cu,Cl powders with various amount of Cu addition.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of high-field EL was proposed to result from the intensification of the electric field near a ZnS-Cu x S contact, and the induction of the tunneling charge carriers to activate the luminescence centers, e.g. Cu, Mn [2,3]. The precipitated Cu x S phase, which has been observed by Ono et al [4] and our group [5] by electron microscopy and optical analysis, is crucial to EL emission.…”
Section: Introductionmentioning
confidence: 70%
“…According to the bipolar field emission model proposed by Fischer [2,3], conductive impurities such as Cu x S are necessary for luminescent ZnS particles to intensify the electric field, and to allow holes and electrons to recombine with radiation in the luminescent centers. Nien et al have also shown that Cu x S is crucial for EL phosphor powders [5,11].…”
Section: Resultsmentioning
confidence: 99%
“…2, the average size of the phosphor powder was approximately 5µm, indicating that the whole powder particle can be excited by photons with a wavelength of 343nm. However, according to the bipolar field emission model proposed by Fischer [16] and our previous studies [7][8][9], conductive Cu x S precipitates are necessary for luminescent ZnS particles to intensify the electric field and to allow tunneling electrons to recombine with radiation in luminescent centers. This is shown per the dependence of emission intensity on the electric field shown in Fig.…”
Section: Resultsmentioning
confidence: 95%